2012
DOI: 10.1136/emermed-2012-201248
|View full text |Cite
|
Sign up to set email alerts
|

Improving the diagnosis of central nervous system infections in adults through introduction of a simple lumbar puncture pack

Abstract: This study has demonstrated that the introduction of a simple low-cost LP pack into a busy acute medical setting can improve the diagnosis of CNS infections and, thus, guide treatment. Further work is needed to see if these results are more widely reproducible, and to examine the clinical, health and economic impact on overall management of patients with suspected CNS infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The use of pre-prepared LP packs, with all the necessary sampling tubes may increase the diagnostic yield. 96 Often inappropriately small volumes of CSF are taken limiting the number of investigations that can be performed. As CSF is produced at a rate of approximately 22 ml/h (similar to urine) amounts of at least 15 ml can be safely removed from adults.…”
Section: Csfmentioning
confidence: 99%
“…The use of pre-prepared LP packs, with all the necessary sampling tubes may increase the diagnostic yield. 96 Often inappropriately small volumes of CSF are taken limiting the number of investigations that can be performed. As CSF is produced at a rate of approximately 22 ml/h (similar to urine) amounts of at least 15 ml can be safely removed from adults.…”
Section: Csfmentioning
confidence: 99%
“…Where guidelines were given in summary format or further multimedia material is available, a hyperlink to the full online guideline is provided. In a similar way to our previous projects, in which we have found that interventions that reduce the time required from doctors have the greatest impact, the app does not require any additional effort from the doctor than simply reading the guidelines they want to read anyway [15,16]. Indeed, by making them readily available and clearly indexed, it is easier for the doctor to use the app to read a section of the guidelines than it is to perform an internet search, then find the website, then find the document, then download the PDF, then scroll through to find the page of interest.…”
Section: Construction and Contentmentioning
confidence: 86%
“…From previous work we have found that simple interventions, such as providing the appropriate bottle for virus identification or for cancer cell identification within the kits doctors use when performing a lumbar puncture, we could increase the identification of viruses and cancer cells [15,16]. Although most doctors knew the importance of sending these types of sample, making it less time-consuming to collect them resulted in real changes in practice and disease identification.…”
Section: Introductionmentioning
confidence: 99%
“…This may occur through bacteremia with secondary seeding of the CNS or through direct infection associated with instrumentation. For example, patients with leptomeningeal malignancies often require a reservoir for intraventricular administration of chemotherapy and are therefore at risk for meningeal infection with both normal skin microbiota and hospital-acquired bacteria through inoculation into the cerebrospinal fluid (40,41). Organisms associated with hospital-acquired central nervous system infections include methicillin-resistant S. aureus, vancomycin-resistant Enterococcus, enteric bacteria, Pseudomonas aeruginosa, and multidrug-resistant Acinetobacter (42).…”
Section: Cns Pathogens Bacteria Hospital-acquired Infectionsmentioning
confidence: 99%
“…Standard testing should include cell count and differential, glucose, and protein, as well as stains and cultures for bacteria, fungi, and mycobacteria (40). Neutropenic patients with bacterial meningitis may have normal cell counts, making the diagnosis in this population particularly challenging (9).…”
Section: Csf Sample Collection and Processingmentioning
confidence: 99%